Caring for animals - Gogerly, Liz (Chicago, Ill Heinemann Library, 2013)
All around the world there are charities trying to improve the lives of endangered, ill, and rescued animals. This book looks at the efforts of animal charities and their workers and volunteers, with exciting stories and case studies, and gives advice on how readers can get involved
A gift from book Africa
The World Around us
1 2 13 15
Keywords: Animal shelters; Animal welfare